Factors Influencing Vocational High School Graduates' Pathways to Higher Education, Civil Service, and Entrepreneurship: A Study in the East Coast Region of Aceh: English - M, Syukurdi; Badaruddin; Lubis, Suwardi; Charloq (CV. ARGA FARMA, 2026)
Vocational high school graduates in the East Coast Region of Aceh face notable challenges in deciding whether to continue their education or enter the workforce. This study analyzes the factors influencing their decisions to pursue higher education, careers in public service (police, military, civil service), or entrepreneurship. A Simple Linear Regression analysis reveals that 92.43% of graduates opt for higher education or public service roles, while 54.45% choose entrepreneurship. The preference for higher education and public service is driven by the desire for socioeconomic mobility, with familial and environmental influences playing critical roles. The findings highlight the need for targeted policies to address the low entrepreneurial interest among vocational graduates, particularly by reducing barriers such as lack of resources and mentorship. Aligning vocational training programs with labor market demands can better support graduates in making informed career decisions. These insights contribute to improving vocational education outcomes and fostering regional economic development.